Transition between preclinical and clinical training: Perception of dental students regarding the adoption of ergonomic principles - Hallak, Júlia Carrer [UNESP]; de Souza Ferreira, Franciele [UNESP]; de Oliveira, Caroline Anselmi [UNESP]; Pazos, Júlia Margato [UNESP]; da Costa Neves, Tamíris [UNESP]; Garcia, Patrícia Petromilli Nordi Sasso [UNESP] (Public Library of Science (PLoS), 2023)
Objective This study aimed to evaluate the perceptions of third-year dental students regarding the application of ergonomic principles in the transition between preclinical and clinical training in Restorative Dentistry. Methods We conducted a qualitative observational cross-sectional study. The sample consisted of forty-six third-year dental students at São Paulo State University (Unesp), School of Dentistry, Araraquara. Data was collected using an individual interview recorded on a digital voice recorder. A script containing questions related to the process of adaptation of students to clinical care with a view to ergonomic work posture was used. Data analysis was based on the quali-quantitative technique of Discourse of the Collective Subject (DCS), using Qualiquantisoft®. Results Most students (97.80%) perceived the need for an adaptation period in the transition from the preclinic to the clinic regarding ergonomic posture requirements; a part of them (45.65%) claimed that they still could not adapt, primarily due to the difference between the laboratory and clinic in the workstation (50.00%). Some students suggested longer preclinical training in a clinical environment to facilitate this transition (21.74%). The dental stool (32.60%) and the dental chair (21.74%) were the external factors that contributed most to making this transition difficult. The difficulty of the restorative dentistry procedure (10.87%) also interfered with posture. Additionally, the most challenging ergonomic posture requirements in the transition period were maintaining 30 to 40 cm between the patient’s mouth and operator’s eyes (45.65%), positioning the patient in the dental chair correctly (15.22%), and working with the elbows close to the body (15.22%). Conclusion Most students perceived the need for an adaptation period in the preclinical transition to the clinic, attributing difficulties to adopt the ergonomic posture requirements, to use the workstation and to perform the procedures on real patients.